Molecular Evolution of Cell Division Proteins FtsA, FtsL, and FtsZ in Bacteria: A Phylogenetic Analysis - Rohini, K. (Malaysian Journal of Microbiology, 2010)
In the past 16s rRNA gene sequencing has been used to find out the evolutionary pattern and the phylogenetic relationship among bacteria. Despite its accuracy, 16S rRNA gene sequence analysis lacks widespread use beyond the large reference laboratories because of technical and cost considerations. The rapid development of the field of proteomics has now been very helpful in finding the phylogenetic relationship of microorganisms. An attempt has been made in this study to find out the molecular evolution of three cell division proteins FtsZ, FtsA and FtsL among certain bacteria and possibility of studying their phylogenetic relationship using various proteomics databases and tools. For the present study various economically and medically important bacteria were selected. The amino acid residue sequence of the three cell division proteins FtsZ, FtsA and FtsL were retrieved from UniprotKB database. The sequences thus obtained for each cell division protein were subjected to Multiple Sequence analysis in ClustalW database. The molecular evolution and phylogenetic study has been performed using TreeDomViwer. The study clearly revealed that the cell division proteins do follow a definitive evolutionary pattern and is based on gram staining character rather than the morphology. The present study has also clearly shown that the important conserved protein sequences can be very useful to study the phylogeny of bacteria.